Implementasi Compatibility Layer Pada Jaringan Server Diskless Berbasis Lubuntu 18.04 LTS - Farid Jatri Abiyyu; Ibnu Ziad; Ade Silvia Handayani (Elkom : Jurnal Elektronika dan Komputer, 2020)
Diskless server is a cluster computer network which uses SSH (Secure Shell) protocol to grant the client an access to the host's directory and modify it's content so that the client don't need a hardisk (Thin Client). One way to design a diskless server is by utilizing "Linux Terminal Server Project", an open source-based script for Linux. However, using Linux has it own drawback, such as it can't cross platform for running an aplication based on Windows system which are commonly used. This drawback can be overcomed by using a compatibility layer that converts a windows-based application's source code. The data which will be monitored is the compatibility layer implementation's result, and the throughput, packet loss, delay, and jitter. The result of measurement from those four parameters resulting in "Excellent" for throughput, "Perfect" for packet loss and delay, and "Good" for jitter.